Tungsten compound composite titanium oxide
Patent Information
- Application Number
- JP2025058917
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0018】 本発明は、新たに、タングステン化合物複合酸化チタンを提供する事が出来る。
Smart Images

Figure 2026166146000001 
Figure 2026166146000002
Abstract
Description
[Technical Field]
[0001] This invention relates to tungsten compound composite titanium oxide. [Background technology]
[0002] Patent Document 1 discloses a titanium oxide sol containing tungsten oxide in which, when the color quality index b value of the reflected color before ultraviolet irradiation is b1 and the color quality index b value of the reflected color after ultraviolet irradiation is b2, b2 - b1 < 0. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2005-231935 [Overview of the project] [Problems that the invention aims to solve]
[0004] The present invention aims to provide a new tungsten compound composite titanium oxide. [Means for solving the problem]
[0005] Titanium dioxide possesses photocatalytic properties, exhibiting environmental purification and antibacterial effects.
[0006] There is a demand for improved visible light responsiveness in titanium dioxide. Methods for imparting visible light responsiveness include adding tungsten oxide. Conventional methods include adding tungsten oxide to a titanium dioxide film afterwards, or adding tungsten oxide particles to titanium dioxide to create a composite. However, conventional methods lead to a breakdown of dispersibility and aggregation of titanium dioxide (tungsten oxide particles), resulting in increased particle size and a significant decrease in the transparency of the coating film.
[0007] This invention encompasses the following tungsten compound composite titanium oxides.
[0008] Section 1. Tungsten compound composite titanium oxide, (A) Titanium dioxide and (B) Contains a tungsten compound, The titanium oxide (A) has an average primary particle size of 0.1 nm to 50 nm. The tungsten compound (B) has an average primary particle size of 0.1 nm to 5 nm. Tungsten compound composite titanium oxide.
[0009] Section 2. The tungsten compound composite titanium oxide according to item 1, wherein the particle size ratio ((a1) / (b1)) of the average primary particle size (a1) of the titanium oxide (A) and the average primary particle size (b1) of the tungsten compound (B) is (a1) / (b1) = 1 to 100.
[0010] Section 3. The tungsten compound composite titanium oxide according to item 1, wherein the molar ratio ((b2) / ((a2)+(b2))) of the number of moles of titanium atoms (a2) in the (A) titanium oxide to the number of moles of tungsten atoms (b2) in the (B) tungsten compound is (b2) / ((a2)+(b2)) = 0.05 to 0.9.
[0011] Section 4. The (A) titanium dioxide is a tungsten compound composite titanium dioxide as described in items 1 to 3 above, wherein the crystalline system is anatase.
[0012] Section 5. A coating agent comprising tungsten compound composite titanium oxide as described in any one of items 1 to 3 above.
[0013] Section 6. A method for producing tungsten compound composite titanium oxide according to any one of the above items 1 to 3, (1) A step of synthesizing a composite sol of a Ti compound and a tungsten (W) compound in a solvent. (2) After step (1), a step of separating the solvent and the powder, (3) After step (2), a heat treatment is performed to crystallize the Ti compound and the W compound A method for producing a tungsten compound-composited titanium oxide, comprising the above step.
[0014] Item 7. The method for producing a tungsten compound-composited titanium oxide according to any one of the preceding Items 1 to 3, wherein (1) Acetic acid and water are added to titanium tetraisopropoxide, and (NH₄) 10 (H₂W 12 O 42 )·4H₂O is mixed in accordance with the molar ratio of titanium tetraisopropoxide, followed by heating and stirring to prepare a uniform titania sol, and (2) The titania sol obtained in step (1) is subjected to ultrasonic dispersion for clarification, then the titania sol is subjected to dispersion treatment with a high-pressure dispersing apparatus, and further heat-treated to obtain a powder A method for producing a tungsten compound-composited titanium oxide, comprising the above steps.
[0015] The tungsten compound-composited titanium oxide of the present invention is a highly transparent material by nano-dispersing titania and tungsten.
[0016] The tungsten compound-composited titanium oxide of the present invention is a material in which titanium oxide (TiO₂) and tungsten are composited by a sol-gel method. The tungsten compound-composited titanium oxide of the present invention has high transparency and high photocatalytic activity.
[0017] The synthesis process of the tungsten compound-composited titanium oxide of the present invention is optimized, and by nano-dispersing the tungsten compound on the titanium oxide, the dispersibility of the tungsten compound-composited titanium oxide is improved to the utmost limit. The tungsten compound-composited titanium oxide of the present invention is a material with higher photocatalytic activity and higher transparency than conventional materials.
Effects of the Invention
[0018] The present invention can newly provide a tungsten compound-composited titanium oxide. [Modes for carrying out the invention]
[0019] The present invention will be described in detail below.
[0020] The embodiments illustrating the present invention are intended to provide a better understanding of the invention's intent and, unless otherwise specified, do not limit the scope of the invention.
[0021] In this specification, "contains" and "include" are concepts that encompass all of "comprise," "consist essentially of," and "consist of."
[0022] In this specification, when a numerical range is indicated as "A to B", it means "greater than or equal to A and less than or equal to B".
[0023] In this specification, when using indications such as parts, percentages, etc., they represent parts by mass, parts by weight, mass%, or weight% (wt%).
[0024] [1] Tungsten compound composite titanium oxide Titanium dioxide possesses photocatalytic properties, exhibiting environmental purification and antibacterial effects.
[0025] There is a demand for improved visible light responsiveness in titanium dioxide. Methods for imparting visible light responsiveness include adding tungsten oxide. Conventional methods include adding tungsten oxide to a titanium dioxide film afterwards, or adding tungsten oxide particles to titanium dioxide to create a composite. However, conventional methods lead to a breakdown of dispersibility and aggregation of titanium dioxide (tungsten oxide particles), resulting in increased particle size and a significant decrease in the transparency of the coating film.
[0026] The tungsten compound composite titanium oxide of the present invention (A) Titanium dioxide and (B) Contains a tungsten compound, (A) Titanium dioxide has an average primary particle size of 0.1 nm to 50 nm. (B) The tungsten compound has an average primary particle size of 0.1 nm to 5 nm.
[0027] The tungsten compound composite titanium oxide of the present invention is preferably, The particle size ratio ((a1) / (b1)) of (A) the average primary particle size (a1) of titanium dioxide and (B) the average primary particle size (b1) of the tungsten compound is (a1) / (b1) = 1 to 100.
[0028] The tungsten compound composite titanium oxide of the present invention preferably has a molar ratio ((b2) / ((a2)+(b2))) of (b2) / ((a2)+(b2)) = 0.05 to 0.9, and more preferably 0.1 to 0.5.
[0029] The tungsten compound composite titanium oxide of the present invention preferably has (A) titanium oxide having anatase crystal system.
[0030] The present invention encompasses coating agents containing the tungsten compound composite titanium oxide of the present invention.
[0031] The tungsten compound composite titanium oxide of the present invention is a highly transparent material due to the nano-dispersion of titania and tungsten.
[0032] The tungsten compound composite titanium oxide of the present invention is a composite material of titanium oxide (TiO2) and tungsten, produced by the sol-gel method. The tungsten compound composite titanium oxide of the present invention has high transparency and high photocatalytic activity.
[0033] The synthesis process for the tungsten compound composite titanium oxide of the present invention has been optimized, and by nano-dispersing the tungsten compound on titanium oxide, the dispersibility of the tungsten compound composite titanium oxide has been improved to the extreme. Compared to conventional materials, the tungsten compound composite titanium oxide of the present invention has higher photocatalytic activity and higher transparency.
[0034] (1-1)(A)Ti compound The tungsten compound composite titanium oxide of the present invention contains (A)Ti compound, and the average primary particle size of the (A)Ti compound is 1 nm to 50 nm.
[0035] Water, inorganic acids, and liberated organic acids generally evaporate almost completely below 200°C.
[0036] (A) The titania compound (titania nanoparticles) of the Ti compound (preferably titania-coated silver) has acetyl groups (CH3-C(=O)-, Ac), acetoxy groups (acetyloxy group, CH3-C(=O)-O-, AcO), etc. bonded to at least some of the titanium atoms present on its surface, and these gradually detach in the range of 200°C to 600°C. For example, in the case of acetoxy groups, they gradually detach in the range of 200°C to 600°C, with a peak at approximately 260°C.
[0037] In tungsten compound composite titanium oxide, (A) the average primary particle size of the Ti compound is 1 nm to 50 nm, preferably 1 nm to 20 nm, and more preferably 1 nm to 10 nm. By adjusting the average primary particle size of the Ti compound to this range, it becomes possible to partially coat the silver with Ti. The titania nanoparticles can form a film with higher visible photocatalytic activity and higher transparency. The Ti compound has excellent coatability.
[0038] The average primary particle size of the Ti compound (titania nanoparticles) is measured by electron microscopy (TEM) observation. The average primary particle size is calculated as follows:
[0039] First, adjust the magnification of the electron microscope to a level where the particles are clearly visible and take an image. Load the captured image into image processing software such as WINROOF. Then, use the shape measurement function to evaluate the shape of the particles. The equivalent circle diameter (Heywood system) calculated therein is defined as the particle diameter of the particle. Perform this operation on any 20 particles and define the average as the average primary particle diameter.
[0040] The specific surface area of the Ti compound is preferably 150 m². 2 / g~500m 2 It is / g, more preferably 200m 2 / g~400m 2 The value is / g. By adjusting the specific surface area of the Ti compound to this range, it is possible to coat the Ti compound with metals (silver and copper) to an appropriate degree, partially coating the silver with Ti. The Ti compound exhibits high visible photocatalytic activity.
[0041] The specific surface area of the Ti compound is measured by the BET method.
[0042] The concentrations of N, Cl, and S in the Ti compound can be preferably 0 to 5,000 ppm, more preferably 0 to 1,000 ppm. By adjusting the concentrations of N, Cl, and S in the Ti compound to this range, corrosion of the substrate can be suppressed. The concentrations of N, Cl, and S in the Ti compound mean that impurities derived from acidic Ti compound precursors such as TiCl4 and TiOSO4 are absent or present in very small amounts.
[0043] The concentrations of elements N, Cl, and S are measured by WDX (X-ray fluorescence).
[0044] The elemental concentrations of the Ti compound are measured using methods such as ICP emission spectrometry or ICP mass spectrometry.
[0045] The crystalline form of the Ti compound is preferably the anatase form. The Ti compound (titania nanoparticles) is preferably the anatase form, more preferably a crystalline form containing 90% or more of the anatase form, and even more preferably a crystalline form that contains no crystalline forms other than the anatase form and is 100% anatase form. By using the anatase form of the Ti compound, the visible photocatalytic activity of the Ti compound is improved.
[0046] (1-2)(B) Tungsten compounds The tungsten compound composite titanium oxide of the present invention contains (B) a tungsten compound (W compound), and the average primary particle size of the (B) tungsten compound is 0.1 nm to 5 nm.
[0047] In tungsten compound composite titanium oxide, the average primary particle size of the (B)W compound is 0.1 nm to 5 nm, preferably 0.1 nm to 3 nm, and more preferably 0.1 nm to 1 nm. The average primary particle size of the W compound allows for uniform compounding when composited with Ti. The W compound (particles) can form a film with higher visible photocatalytic activity and higher transparency. The W compound has excellent coatability.
[0048] The average primary particle size of compound W is measured by electron microscopy (TEM). The average primary particle size is calculated as follows:
[0049] First, adjust the magnification of the electron microscope to a level where the particles are clearly visible and take an image. Load the captured image into image processing software such as WINROOF. Then, use the shape measurement function to evaluate the shape of the particles. The equivalent circle diameter (Heywood system) calculated therein is defined as the particle diameter of the particle. Perform this operation on any 20 particles and define the average as the average primary particle diameter.
[0050] The elemental concentrations of the W compound are measured by methods such as ICP emission spectrometry or ICP mass spectrometry.
[0051] (1-3) Coating agent The present invention encompasses coating agents containing the tungsten compound composite titanium oxide of the present invention.
[0052] The coating film of the present invention is preferably prepared as a paint by adjusting its viscosity according to its application. When used for coating by spin coating, dip coating, spraying, etc., the viscosity is preferably adjusted to a low viscosity. When used for coating by brush application, squeegeeing, etc., the viscosity is preferably adjusted to a higher level. When used for coating by screen printing, the viscosity is preferably adjusted to an even higher level to suppress fluidity.
[0053] The coating film of the present invention enables a dense coating.
[0054] This invention includes an antibacterial and antiviral coating film.
[0055] Painted products having a coating film are not particularly limited and include, for example, building materials, building exteriors, building interiors, window frames, window glass, various lenses, structural members, building equipment such as houses, cooking utensils, textile products, furniture, displays, display protective films, plumbing components, covers and window glass for vehicle lighting, machinery or exteriors of articles, dust covers and coatings, display equipment and their covers, traffic signs, various display devices, advertising towers and other display objects, sound barriers for roads and railways, bridges, guardrail exteriors and coatings, tunnel interiors and coatings, insulators, solar cell covers, solar water heater collector covers and other exterior parts of electronic and electrical equipment used outdoors, especially transparent members, vinyl greenhouses, greenhouses and the like.
[0056] (1-4)(A) Particle size ratio of (a1) average primary particle size of titanium dioxide to (B) average primary particle size of tungsten compound ((a1) / (b1)) In the tungsten compound composite titanium oxide of the present invention, the particle size ratio ((a1) / (b1)) of (A) the average primary particle size (a1) of titanium oxide to (B) the average primary particle size (b1) of the tungsten compound is preferably (a1) / (b1) = 1 to 100.
[0057] (1-5) The molar ratio of (a2) moles of (A) titanium dioxide to (b2) moles of (B) tungsten compound ((b2) / ((a2)+(b2))) The tungsten compound composite titanium oxide of the present invention preferably has a molar ratio ((b2) / ((a2)+(b2))) of (b2) / ((a2)+(b2)) = 0.05 to 0.9, and more preferably 0.1 to 0.5.
[0058] [2] Method for producing tungsten compound composite titanium oxide The present invention provides a method for producing tungsten compound composite titanium oxide, and is a method for producing tungsten compound composite titanium oxide according to the present invention. (1) a step of synthesizing a composite sol of a Ti compound and a tungsten (W) compound in a solvent (2) a step of separating the solvent and the powder after step (1), and (3) a step of performing heat treatment after step (2) to crystallize the Ti compound and the W compound is included.
[0059] The method for producing the tungsten compound-composited titanium oxide of the present invention preferably comprises: (1) adding acetic acid and water to titanium tetraisopropoxide, mixing (NH4) 10 (H2W 12 O 42 )·4H2O according to the molar ratio of titanium tetraisopropoxide, and then performing heating and stirring to prepare a uniform titania sol, and (2) subjecting the titania sol obtained in step (1) to ultrasonic dispersion for clarification, then subjecting the titania sol to dispersion treatment with a high-pressure dispersing apparatus, and further performing heat treatment to obtain a powder is included.
[0060] (1) Step of synthesizing a composite sol of a Ti compound and a W compound in a solvent. The method for producing the tungsten compound-composited titanium oxide of the present invention comprises: (1) a step of synthesizing a composite sol of a Ti compound and a tungsten (W) compound in a solvent.
[0061] (Ti compound) The Ti compound (titanium-containing substance) is preferably a substance that becomes titanium oxide upon heating. The titanium-containing substance is preferably titanium oxide and / or a titanium oxide precursor, more preferably titanium oxide; titanium hydroxide; titanium alkoxide; titanium halides such as titanium trichloride and titanium tetrachloride (in particular, those neutralized with a base); metallic titanium and the like are used.
[0062] From the viewpoint of the dispersibility, coatability, and visible photocatalytic properties of the resulting titania, the titanium-containing substance is preferably titanium alkoxide, titanium hydroxide, or titanium halide (especially those neutralized with a base). From the viewpoint of purity, dispersibility, coatability, transparency, and visible photocatalytic properties, the titanium-containing substance is more preferably titanium alkoxide.
[0063] The titanium alkoxide is preferably titanium tetraisopropoxide, titanium tetra-n-butoxide, titanium tetra-n-propoxide, or titanium tetraethoxide. From the viewpoint of cost, water solubility of by-products, applicability, and visible photocatalytic properties, titanium tetraisopropoxide is more preferable.
[0064] The Ti compound may be at least one compound selected from the group consisting of the aforementioned Ti compounds, and these Ti compounds may be used individually or two or more may be mixed (blended) depending on the purpose.
[0065] The average primary particle size of the Ti compound is preferably 100 nm or less, and more preferably 50 nm or less. There is no specific lower limit set for the average primary particle size of the titanium-containing material, but it is preferably about 1 nm. If the particle size is large, it is preferably ground dry or wet using a planetary ball mill, paint shaker, etc.
[0066] The average primary particle size of Ti compounds (solids such as titanium oxide, metallic titanium, and titania nanoparticles) is measured by electron microscopy (TEM). The average primary particle size is calculated as follows:
[0067] First, adjust the magnification of the electron microscope to a level where the particles are clearly visible and take an image. Load the captured image into image processing software such as WINROOF. Then, use the shape measurement function to evaluate the shape of the particles. The equivalent circle diameter (Heywood system) calculated therein is defined as the particle diameter of the particle. Perform this operation on any 20 particles and define the average as the average primary particle diameter.
[0068] (W compound) The tungsten (W) compound (a substance containing W) is preferably a substance that becomes WO3 upon heating. The substance containing W is preferably WO3 and / or a WO3 precursor, and more preferably WO3; tungsten hydroxide; tungsten alkoxide; tungsten salt; metallic tungsten, etc.
[0069] The substance containing tungsten (W) is preferably an ammonium salt of tungstic acid, from the viewpoint of the dispersibility, coating properties, solubility in water, and visible photocatalytic properties of the resulting tungsten. The substance containing W is more preferably (NH4)10(H2W) 12 O 42 )·4H2O. The W compound may be at least one compound selected from the group consisting of the W compounds, and these W compounds may be used individually, or two or more may be mixed (blended) depending on the purpose.
[0070] (Acid used in the reaction) The acid used in the reaction is an organic acid, and a volatile acid is preferred; therefore, a chemical formula C is preferred. n H 2n+1 Monocarboxylic acids represented by COOH(n=0~3) (monocarboxylic acids with 1 to 4 carbon atoms), hydroxycarboxylic acids with 2 to 3 carbon atoms, etc. are used.
[0071] From the viewpoint of volatility, toxicity, and degradability, the monocarboxylic acids are preferably formic acid with n=0 and acetic acid with n=1.
[0072] The hydroxycarboxylic acid is preferably glycolic acid, lactic acid, etc., and more preferably acetic acid, glycolic acid, lactic acid, etc., from the viewpoint of water solubility and odor.
[0073] The organic acid may be at least one compound selected from the group consisting of the aforementioned organic acids, and these organic acids may be used individually or two or more may be mixed (blended) depending on the purpose.
[0074] The amount of organic acid used is adjusted so that, from the viewpoint of dispersibility, coatability, transparency, visible photocatalytic properties, and cost, the number of moles of acyloxy groups in the Ti compound is preferably 1.5 moles or more, and particularly preferably 2 moles or more, per mole of titanium. The more organic acid used, the better the long-term stability, coatability, transparency, etc. can be improved. There is no particular upper limit to the amount of organic acid used, but it is preferably adjusted so that the number of moles of acyloxy groups in the Ti compound is 10 moles or less per mole of titanium.
[0075] The concentration of the organic acid in the dispersion is preferably 0.02 mol / L to 10 mol / L, and more preferably 0.1 mol / L to 7 mol / L, from the viewpoints of dispersibility, coatability, transparency, visible photocatalytic properties, and cost.
[0076] The reaction solvent is preferably an aqueous solvent such as water, mainly composed of (preferably 50% by mass or more). The reaction solvent may also contain alcohol or ester during the reaction.
[0077] When titanium tetraisopropoxide is used as the reaction solvent, isopropyl alcohol is produced by reaction with organic acids. Isopropyl esters of organic acids may be produced by heating. Alcohols or esters may be added to the dispersion, or they may be generated in the system. Alcohols or esters may be removed by heating in an open system below 100°C, by reducing the pressure, or they may remain in the reaction solution.
[0078] When alcohol is present in the dispersion, the average primary particle size of the resulting Ti compound (titania nanoparticles) tends to decrease. Therefore, alcohol may be intentionally added to control the average primary particle size.
[0079] The pH of the dispersion is preferably 2 or higher and less than 6, and more preferably 2.1 to 5, from the viewpoint of preventing corrosion of the equipment, ensuring safety during handling, and maintaining dispersibility.
[0080] The method for preparing the dispersion is not particularly limited; the Ti compound, organic acid, and water (solvent) may be mixed simultaneously or sequentially. In mass production, from the viewpoint of preventing aggregation and the formation of large clumps, and facilitating continued stirring, it is preferable to mix the organic acid and water (solvent) first, and then add the titanium-containing substance while stirring. In laboratory scale, it is preferable to mix the titanium-containing substance and the organic acid first, and then add the water while stirring.
[0081] (2) A step to separate the solvent from the powder after step (1) The present invention provides a method for producing tungsten compound composite titanium oxide. (2) After step (1), the process includes a step of separating the solvent from the powder.
[0082] The slurry prepared in step (1) is separated into a solvent and a powder. The solvent is separated and the powder is recovered by methods such as centrifugation and filtration. Then, the powder (solid content) is dried at 60°C for 1 hour to obtain a composite powder of tungsten (W) compound and titanium (Ti) compound.
[0083] (3) After step (2), a heat treatment is performed to crystallize the Ti compound and the W compound. The present invention provides a method for producing tungsten compound composite titanium oxide. (3) After step (2), the process includes a step of performing heat treatment to crystallize the titanium (Ti) compound and the tungsten (W) compound.
[0084] After step (2), the W composite titania powder is heat-treated to obtain W composite titania powder.
[0085] The heat treatment temperature is preferably 300°C or higher, more preferably 400°C or higher, and even more preferably 600°C or higher. Heat treatment in this temperature range promotes the crystallization of Ti and W compounds.
[0086] The heat treatment temperature is preferably 1 hour or longer. By performing the heat treatment for 1 hour or longer, it is possible for all of the W to crystallize.
[0087] The coating agent of the present invention is preferably prepared as a paint by adjusting its viscosity according to its intended use. When used for coating by spin coating, dip coating, spraying, etc., it is preferably prepared to have a low viscosity. When used for coating by brush application, squeegeeing, etc., it is preferably prepared to have a higher viscosity. When used for coating by screen printing, it is preferably prepared to have an even higher viscosity to suppress fluidity.
[0088] The manufacturing method of the present invention, by means of a new process, makes it possible to produce highly transparent tungsten compound composite titanium oxide by nano-dispersing titania and tungsten. [Examples]
[0089] The present invention will be specifically described below with reference to examples.
[0090] The present invention is not limited to the following specific embodiments.
[0091] [1] Production of tungsten compound composite titanium oxide (W compound composite titanium oxide) [Example 1] (Step 1) Synthesis of the complex sol Add 11.3g of acetic acid to 53.3g of titanium tetraisopropoxide and stir, then add water until the total volume is 400g, and then (NH4) 10 (H2W 12 O 42 )·4H2O was added in such a way that the molar ratio of Ti was W / (Ti+W)=0.5, and then the mixture was stirred for 90 minutes.
[0092] Next, the mixture was heated to 95°C and stirred with a hot stirrer for 9 hours to obtain a homogeneous titania sol. The obtained sol was then subjected to ultrasonic dispersion for 30 minutes to obtain a transparent titania sol.
[0093] (Step 2) Recovery process The titania was filtered through a membrane filter to separate the solution from the solid, and the solid was recovered. This solid was dried at 60°C for 1 hour to obtain a composite powder of W and Ti.
[0094] (Step 3) Heat treatment process The aforementioned W-compound titania powder was heat-treated at 600°C for 3 hours to obtain W-compound titania powder.
[0095] (Step 4) Preparation of coating solution To 2.4 g of the prepared W compound composite titanium dioxide powder, 4.8 g of tetraethyl orthosilicate (TEOS) and 4.8 g of acetic acid were added, and ethanol was added until the total volume reached 300 g. The reactor was then covered to prevent the solvent from evaporating, and the mixture was maintained at 60°C for 1 hour. The hydrolysis of tetraethyl orthosilicate proceeded, yielding a transparent W compound composite titanium dioxide coating solution.
[0096] [Example 2] In Example 2, a W compound composite titanium oxide coating solution was obtained using the same process as in Example 1, except that the amount of additive was adjusted in step 1 so that W / (Ti+W)=0.4.
[0097] [Example 3] In Example 3, a W compound composite titanium oxide coating solution was obtained using the same process as in Example 1, except that the amount of additive was adjusted in step 1 so that W / (Ti+W)=0.3.
[0098] [Example 4] In Example 4, a W compound composite titanium oxide coating solution was obtained using the same process as in Example 1, except that the amount of additive was adjusted in step 1 so that W / (Ti+W)=0.2.
[0099] [Example 5] In Example 5, a W compound composite titanium oxide coating solution was obtained using the same process as in Example 1, except that the amount of additive was adjusted in step 1 so that W / (Ti+W)=0.1.
[0100] [Comparative Example 1] Comparative Example 1 used P25 from Nippon Aerosil and tungsten oxide from Nippon High Purity Chemical as the Ti source, mixing 2.4 g by weight so that the W / (Ti+W) ratio was 0.5. Furthermore, 4.8 g of tetraethyl orthosilicate (TEOS) and 4.8 g of acetic acid were added, and ethanol was added until the total volume reached 300 g. After that, the reactor was covered to prevent the solvent in the reaction solution from evaporating, and the mixture was maintained at 60°C for 1 hour. The coating solution was obtained by the hydrolysis of tetraethyl orthosilicate.
[0101] [2] Evaluation of tungsten compound composite titanium oxide The following evaluations were performed on the tungsten compound composite titanium oxides of the obtained examples and comparative examples.
[0102] (1) Transparency of the dispersion (Measurement of permeability of dispersion) The transparency of the coating composition (dispersion) was measured by transmittance using a UV-Vis spectrometer (Shimadzu UV3400). The transmittance value at a wavelength of 580 nm was defined as the transmittance of the composition.
[0103] The criteria for evaluating the dispersion are as follows: ◎: The dispersion has a transmittance of 80% or more at a wavelength of 580 nm. ×: The dispersion has a maximum transmittance of less than 80%, or precipitation has occurred and separation is visible.
[0104] (2) Photocatalytic activity of the dispersion (Transmittance Ta) A 1 mm thick glass substrate coated (spin-coated) with a dispersion (coating composition) was dried at 120°C, and the transmittance at a wavelength of 587.6 nm (d-line: wavelength close to the absorption peak of methylene blue) was measured using a UV-Vis spectrometer (Shimadzu UV3400). This transmittance is denoted as Ta.
[0105] (Transmittance Tb) Next, a 1 mmol / L methylene blue solution was dropped onto the substrate, dried, and excess solution was removed. The transmittance at 587.6 nm (d-line: wavelength close to the absorption peak of methylene blue) was then measured using a UV-Vis spectrometer (Shimadzu UV3400). This transmittance is denoted as Tb. The value of Tb decreases due to the coloring of the methylene blue, but decomposition occurs due to the photocatalytic effect.
[0106] (degradation activity Tb / Ta) Subsequently, the sample was irradiated with ultraviolet light at a peak wavelength of 352 nm using a black light, and measurements were taken every hour. The time required for Tb / Ta to become > 90% was measured to evaluate the photocatalytic decomposition activity.
[0107] The criteria for determining photocatalytic properties are as follows: ◎: The dispersion reaches a Tb / Ta ratio of 90% within 12 hours. ×: The dispersion takes 12 hours or more for Tb / Ta to reach 90%.
[0108] The results of the examples and comparative examples are shown in the table below.
[0109] [Table 1]
[0110] The tungsten compound composite titanium dioxide of Examples 1-5 exhibited high transparency and high photocatalytic activity.
[0111] The tungsten compound composite titanium oxide in Comparative Example 1 had low transparency.
[0112] [ka]
[0113] [Industrial applicability] The present invention relates to tungsten compound composite titanium oxide, which is a highly transparent material due to the nano-dispersion of titania and tungsten.
[0114] The tungsten compound composite titanium oxide of the present invention is a composite material of titanium oxide (TiO2) and tungsten, produced by the sol-gel method. The tungsten compound composite titanium oxide of the present invention has high transparency and high photocatalytic activity.
[0115] The synthesis process for the tungsten compound composite titanium oxide of the present invention has been optimized, and by nano-dispersing the tungsten compound on titanium oxide, the dispersibility of the tungsten compound composite titanium oxide has been improved to the extreme. Compared to conventional materials, the tungsten compound composite titanium oxide of the present invention has higher photocatalytic activity and higher transparency.
Claims
1. Tungsten compound composite titanium oxide, (A) Titanium oxide and (B) Contains a tungsten compound, The titanium oxide (A) has an average primary particle size of 0.1 nm to 50 nm. The tungsten compound (B) has an average primary particle size of 0.1 nm to 5 nm. Tungsten compound composite titanium oxide.
2. The tungsten compound composite titanium oxide according to claim 1, wherein the particle size ratio ((a1) / (b1)) of the average primary particle size (a1) of the titanium oxide (A) and the average primary particle size (b1) of the tungsten compound (B) is (a1) / (b1) = 1 to 100.
3. The tungsten compound composite titanium oxide according to claim 1, wherein the molar ratio ((b2) / ((a2)+(b2))) of the number of moles of titanium atoms (a2) of the titanium oxide (A) and the number of moles of tungsten atoms (b2) of the tungsten compound (B) is (b2) / ((a2)+(b2)) = 0.05 to 0.
9.
4. The tungsten compound composite titanium oxide according to claims 1 to 3, wherein the titanium oxide (A) has an anatase crystal system.
5. A coating agent comprising tungsten compound composite titanium oxide as described in any one of claims 1 to 3.
6. A method for producing tungsten compound composite titanium oxide according to any one of claims 1 to 3, (1) A step of synthesizing a composite sol of a Ti compound and a tungsten (W) compound in a solvent. (2) A step of separating the solvent and the powder after step (1), and (3) After step (2), heat treatment is performed to crystallize the Ti compound and the W compound. A method for producing tungsten compound composite titanium oxide, including the above.
7. A method for producing tungsten compound composite titanium oxide according to any one of claims 1 to 3, (1) Add acetic acid and water to titanium tetraisopropoxide, (NH 4 ) 10 (H 2 W 12 O 42 )・4H 2 The process involves mixing O according to the molar ratio of titanium tetraisopropoxide, then heating and stirring to create a homogeneous titania sol, and (2) The titania sol obtained in step (1) is ultrasonically dispersed to make it transparent, then the titania sol is dispersed using a high-pressure dispersion device, and further heat-treated to obtain a powder. A method for producing tungsten compound composite titanium oxide, including the above.
Citation Information
Patent Citations
Tungsten oxide-containing titanium oxide sol, method of manufacturing the same, coating material and optical functional body
JP2005231935A